CARMENES input catalog of M dwarfs: VI. A time-resolved Ca II H&K catalog from archival data - Perdelwitz, Volker; Mittag, M.; Tal-Or, L.; Schmitt, J. H. M. M.; Caballero, J. A.; Jeffers, S. V.; Reiners, A.; Schweitzer, A.; Trifonov, T.; Ribas, I.; Quirrenbach, Andreas; Amado, P. J.; et al. (Astronomy and astrophysics, 2021)
Context. Radial-velocity (RV) jitter caused by stellar magnetic activity is an important factor in state-of-the-art exoplanet discovery surveys such as CARMENES. Stellar rotation, along with heterogeneities in the photosphere and chromosphere caused by activity, can result in false-positive planet detections. Hence, it is necessary to determine the stellar rotation period and compare it to any putative planetary RV signature. Long-term measurements of activity indicators such as the chromospheric emission in the Ca II H&K lines ( ) enable the identification of magnetic activity cycles.Aims. In order to determine stellar rotation periods and study the long-term behavior of magnetic activity of the CARMENES guaranteed time observations (GTO) sample, it is advantageous to extract time series from archival data, since the CARMENES spectrograph does not cover the blue range of the stellar spectrum containing the Ca II H&K lines.Methods. We have assembled a catalog of 11 634 archival spectra of 186 M dwarfs acquired by seven different instruments covering the Ca II H&K regime: ESPaDOnS, FEROS, HARPS, HIRES, NARVAL, TIGRE, and UVES. The relative chromospheric flux in these lines, , was directly extracted from the spectra by rectification with PHOENIX synthetic spectra via narrow passbands around the Ca II H&K line cores.Results. The combination of archival spectra from various instruments results in time series for 186 stars from the CARMENES GTO sample. As an example of the use of the catalog, we report the tentative discovery of three previously unknown activity cycles of M dwarfs.Conclusions. We conclude that the method of extracting with the use of model spectra yields consistent results for different instruments and that the compilation of this catalog will enable the analysis of long-term activity time series for a large number of M dwarfs.
Gesehen am 29.10.2021